Penerapan Asas Keadilan dalam Penyelesaian Sengketa Perdata di Indonesia - Danialsyah, Danialsyah (UNES Law Review, 2023)
The goal of this study is to assist the community with case management. Settlement of civil disputes can be carried out through a process in court. The research method used is a descriptive qualitative research approach, namely research on natural objects from experiments. using observational data collection techniques, interviews. Research findings describing the application of Restorative Justice in Indonesia are still limited and face various challenges, such as lack of public understanding of the concept of Restorative Justice, limited resources, and lack of support and coordination between institutions. The findings contribute to an in-depth understanding of the opportunities and barriers for incorporating restorative justice approaches into the civil justice system in Indonesia. Recognition by the community and the judiciary. There are challenges in the implementation of restorative justice, such as the lack of trained human resources and adequate facilities, so improvements and developments are needed for restorative justice to be properly implemented.